Effectiveness of Zakat Management Digitalization Policy On Increasing Zakat, Infaq, and Alms (ZIS) Fund Collection In Indonesia - Syahidah Rahmah (JURNAP: Jurnal Administrasi Publik, 2025)
The digital transformation of zakat management has become an important policy agenda in Indonesia to improve the efficiency, transparency, and accessibility of Islamic social finance institutions. This study aims to analyze the effectiveness of zakat management digitalization policies in increasing the collection of Zakat, Infaq, and Alms (ZIS) funds in Indonesia. The study employed a descriptive qualitative approach using secondary data derived from zakat regulations, digital transformation blueprints, BAZNAS annual reports for the period 2021–2025, and relevant scientific literature. Data were collected through documentation and systematic literature review and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings reveal that digitalization policies have significantly improved ZIS collection through the expansion of digital payment channels, enhancement of transparency and accountability, and integration of management information systems and big data. These innovations have increased public trust, strengthened donor loyalty, and expanded the participation of younger generations in digital philanthropy. From the perspectives of the Technology Acceptance Model, Trust Theory, and Maqasid al-Shariah, digitalization contributes to reducing transaction costs, enhancing institutional legitimacy, and accelerating the distribution of social funds for public welfare. Nevertheless, several challenges remain, including digital inequality, uneven technological capacity among zakat institutions, and cybersecurity concerns. Therefore, future policies should emphasize inclusive digital governance, digital literacy enhancement, and institutional capacity building to ensure equitable and sustainable development of zakat management. Overall, the study demonstrates that digitalization policies have become a strategic instrument for strengthening Islamic social finance and promoting social welfare in Indonesia.